Breeding in Africa for Africa - International Potato Center (2012)
A major collaborative strengthening of sweetpotato breeding is underway in target countries of the Sweetpotato for Profit and Health lnitiative. Sweetpotato Support Platforms in Eastern, Southern, and West Africa are working with national partners to rapidly develop improved populations and varieties with regional adaptation and desired quality traits, and to build a community of practice using improved breeding methods and tools.